Baldy of Nome - Darling, Esther Birdsall, 1868-1965 (Salt Lake City, UT : Project Gutenberg, 2004)
"Baldy of Nome" by Esther Birdsall Darling is a fictional narrative likely written in the early 20th century. The story centers on a young boy named Ben Edwards and his relationship with Baldy, a rough-coated dog, as they navigate the hardships of life in Alaska, particularly in the dog racing community. The novel explores themes of loyalty, sacrifice, and the bond between humans and dogs, echoing the struggles faced by both the boy and his canine companion. The opening of the book introduces the poignant farewell between Ben and Baldy, as circumstances dictate their separation. The narrative captures the deep emotional connection between the two, highlighting Ben's concerns for Baldy$1 (Bs welfare amidst his own struggles after losing his father. The encounter with the renowned dog driver "Scotty" Allan brings a ray of hope as Ben attempts to find a new home for Baldy, ensuring he would be cared for and potentially trained as a racer. Throughout this opening portion, readers are drawn into the vivid depictions of Alaskan life, the boy's earnestness, and Baldy's loyalty, setting the stage for their adventures in a challenging and often harsh environment. (This is an automatically generated summary.)s
Release date is 2004-03-01
E-text prepared by Charles Aldarondo, Graeme Mackreth, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Dogs -- Folklore